Impact of middle leaders’ competencies on teachers’ technology acceptance in Malaysian TS25 schools - Jeunhan Yip; Kenny S. L. Cheah; Wen Fen Beh (PLoS ONE, 2025)
This study examines how middle leaders’ competencies influence teachers’ technology acceptance in Malaysian TS25 primary schools. The research combines the Middle Leaders’ Competency Model for Education 4.0 (MLCMEdu4.0) and the Teachers’ Technology Acceptance Model (TTAM). Using a cross-sectional survey, data were gathered from 302 teachers in TS25 schools in Kuala Lumpur and analyzed using Structural Equation Modeling (SEM). Results show a significant positive relationship (β = 0.599, p < .001), with middle leaders’ competency accounting for 36% of the variance (R² = .36) in teachers’ technology acceptance. Critical thinking was identified as the most vital middle leadership competency in Education 4.0, followed by entrepreneurial skills and collaboration. Among factors influencing teachers’ technology acceptance, perceived ease of use, perceived usefulness, and facilitation conditions were most impactful. This study highlights the critical role of middle leaders in supporting technology acceptance, especially in Malaysia’s educational reform context. It highlights the need for targeted professional development programs and clear role definitions for middle leaders to enhance their influence on technology acceptance. Future studies should explore these dynamics across varied educational contexts and adopt longitudinal designs to assess the long-term effects of middle leadership on technology acceptance.